Combination of graphene oxide–silver nanoparticle nanocomposites and cisplatin enhances apoptosis and autophagy in human cervical cancer cells - Yuan YG (Dove Medical Press, 2017)
Yu-Guo Yuan,1,2 Sangiliyandi Gurunathan3 1College of Veterinary Medicine/Animal Science and Technology/Jiangsu Co-Innovation Center for Prevention and Control of Important Animal Infectious Diseases and Zoonosis, Yangzhou University, Yangzhou, Jiangsu, China; 2Jiangsu Key Laboratory of Integrated Traditional Chinese and Western Medicine for Prevention and Treatment of Senile Diseases, Yangzhou University, Yangzhou, China; 3Department of Stem Cell and Regenerative Biotechnology, Konkuk University, Seoul, Republic of Korea Background: Cisplatin (Cis) is a widely used chemotherapeutic drug for treating a variety of cancers, due to its ability to induce cell death in cancer cells significantly. Recently, graphene and its modified nanocomposites have gained much interest in cancer therapy, due to their unique physicochemical properties. The objective of this study was to investigate the combination effect of Cis and a reduced graphene oxide–silver nanoparticle nanocomposite (rGO-AgNPs) in human cervical cancer (HeLa) cells.Materials and methods: We synthesized AgNPs, rGO, and rGO-AgNP nanocomposites using C-phycocyanin. The synthesized nanomaterials were characterized using various analytical techniques. The anticancer properties of the Cis, rGO-AgNPs, and combination of Cis and rGO-AgNPs were evaluated using a series of cellular assays, such as cell viability, cell proliferation, LDH leakage, reactive oxygen species generation, and cellular levels of oxidative and antioxidative stress markers such as malondialdehyde, glutathione, SOD, and CAT. The expression of proapoptotic, antiapoptotic, and autophagy genes were measured using real-time reverse-transcription polymerase chain reaction.Results: The synthesized AgNPs were well dispersed, homogeneous, and spherical, with an average size of 10 nm and uniformly distributed on graphene sheets. Cis, GO, rGO, AgNPs, and rGO-AgNPs inhibited cell viability in a dose-dependent manner. The combination of Cis and rGO-AgNPs showed significant effects on cell proliferation, cytotoxicity, and apoptosis. The combination of Cis and rGO-AgNPs had more pronounced effects on the expression of apoptotic and autophagy genes, and also significantly induced the accumulation of autophagosomes and autophagolysosomes, which was associated with the generation of reactive oxygen species.Conclusion: Our findings substantiated rGO-AgNPs strongly potentiating Cis-induced cytotoxicity, apoptosis, and autophagy in HeLa cells, and hence rGO-AgNPs could be potentially applied to cervical cancer treatment as a powerful synergistic agent with Cis or any other chemotherapeutic agents. Keywords: cisplatin, graphene oxide–silver nanoparticles nanocomposites, oxidative stress, cell viability, apoptosis, autophagy